Dietary n‐3 long chain polyunsaturated fatty acids affect the serum biochemical parameters, lipid‐metabolism‐related of gene expression and intestinal health of juvenile hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatu). (8th May 2021) - An, Wenqiang; Dong, Xiaohui; Tan, Beiping; Yang, Qihui; Chi, Shuyan; Zhang, Shuang; Liu, Hongyu; Yang, Yuanzhi
Abstract: To determine the effects of dietary n‐3 long chain polyunsaturated fatty acids (n‐3 LC‐PUFA) on lipid metabolism and intestinal health of juvenile hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatu ), an 8‐week feeding experiment was carried out using six isoproteic and isolipidic formula diets containing 0.65% (control), 1.00%, 1.35%, 1.70%, 2.05% and 2.40% n‐3 LC‐PUFA (dry matter). The results showed that the serum triglyceride and cholesterol reached the minimum in the 1.70% group and 1.35% group, respectively. The serum glucose content of the control group was significantly lower than that of the other groups ( p  < 0.05). Compared with the control group, the expression of hepatic cpt ‐ 1 gene in the 2.05% group and atgl, apob ‐ 100 genes in the 2.40% group reached the maximum and increased significantly, while fas, accα and pparγ genes in the 2.05% and 2.40% groups decreased significantly ( p  < 0.05). The cpt ‐ 1, atgl and pparα gene expression in the muscle increased first and then decreased, reaching the maximum in the 1.70% and 1.35% groups, while the expression of fas and pparγ significantly decreased ( p  < 0.05), reaching the minimum in the 2.40% and 2.05% groups, respectively. Intestinal lipase and trypsin activities in the 2.05% group reached the maximum. In the intestine microbiota, Proteobacteria, Bacteroidetes and Firmicutes were the dominant phyla. The contents of Bacteroidales_S24‐7_group and Lachnospiraceae increased with the addition n‐3 LC‐PUFA. In summary, the moderate dietary n‐3 LC‐PUFA (1.35%–1.70%) could up‐regulate lipid catabolism gene expression and down‐regulate lipid anabolism gene expression; dietary n‐3 LC‐PUFA significantly affected the structural integrity of the proximal intestine and improved the abundance of intestinal probiotics in hybrid grouper.